The impacts of yellow fever on public health: general aspects and its implications in Brazil (Research, Society and Development, 2020)
This study aims to demonstrate the general aspects of Yellow Fever (AF) in Brazil, especially with regard to the epidemiological aspects that directly affect collective health, bringing in its context the outbreak of AF evidenced in Brazil between the years 2016 and 2017, where 778 human cases of AF have been identified, including 262 deaths, according to the World Health Organization (WHO). For this, bibliographic and documentary research was carried out. Searches for contemporary data were carried out, calling attention to the importance of treating AF as a tropical disease, which has a great impact on public health and which deserves constant public policy attention. The results showed that the Brazilian region most affected by AF (2016-2017) was the Southeast. In addition, despite the prevalence of wild AF, the lack of attention and preventive aspects, the elimination of transmission agents, and the expansion of vaccination areas can trigger outbreaks that, in addition to being more frequent, may affect a greater number of people. It is considered, then, the need for environmental and entomological studies for the recognition of receptive areas for wild transmission, and the application of actions in collective health, with a view to combating and preventing the vector, transmitter of AF.